Improving multimedia as a service (MaaS) approach for dynamic multimedia content integration. (1st January 2013) - Lebib, Fatma Zohra; Mellah, Hakima; Monfort, Valérie
Multimedia content is derived from various autonomous, distributed and heterogeneous content sources. Service Oriented Architecture (SOA) is seen as a general answer to data integration problems. In this research work, we extend previous research works based on a model called Multimedia as a Service (MaaS); through which multimedia content providers expose their content. We propose now a method to automatically discover and invoke relevant MaaSs services, which enables dynamic and transparent multimedia content integration according to user's preferences and device capabilities. For that, we propose to enhance the semantics in the MaaSs services description using domain ontology and use the standard Composite Capabilities/Preferences Profile (CC/PP) of W3C to manage the user profile.